Penerapan Relaksasi Otot Progresif Terhadap Tekanan Darah Pada Lansia Dengan Hipertensi Di RSUD dr. Soeratno Gemolong - Amanah Dini Isnaini; Tri Susilowati; Fitria Purnamawati (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Background; Hypertension is the deadliest disease in the world that can affect anyone, both young and old. The highest prevalence of disease in the elderly aged 55-56 years is hypertension with 55.2%. Hypertension if left untreated can cause stroke, myocardial infarction, kidney failure and encephalopathy. One of the non-pharmacological treatment of hypertension with progressive muscle relaxation techniques. Progressive muscle relaxation is a relaxation therapy that can lower blood pressure by tensing and relaxing the muscles. Objective; Knowing the results of implementing progressive muscle relaxation on blood pressure in the elderly at dr. Soeratno Gemolong. Method; using a case study design with the subject of 2 respondents who were treated in the Tulip room at RSUD dr. Soeratno Gemolong was then given the implementation of progressive muscle relaxation for 3 consecutive days with 3 meetings with a duration of 15 minutes. The measuring instrument used for blood pressure uses a digital tensimeter. Results; Provision of progressive muscle relaxation can reduce blood pressure in 2 respondents at RSUD dr. Soeratno. Conclusion; Progressive muscle relaxation has an effect on reducing blood pressure in the elderly who are treated in the tulip room at RSUD dr. Soeratno.